2008
DOI: 10.2337/dc08-0312
|View full text |Cite
|
Sign up to set email alerts
|

Combined Task Delegation, Computerized Decision Support, and Feedback Improve Cardiovascular Risk for Type 2 Diabetic Patients

Abstract: OBJECTIVE -The Diabetes Care Protocol combines task delegation (a practice nurse), computerized decision support, and feedback every 3 months. We studied the effect of the Diabetes Care Protocol on A1C and cardiovascular risk factors in type 2 diabetic patients in primary care.RESEARCH DESIGN AND METHODS -In a cluster randomized trial, mean changes in cardiovascular risk factors between the intervention and control groups after 1 year were calculated by generalized linear models.RESULTS -Throughout the Netherl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 12 publications
1
122
0
3
Order By: Relevance
“…Another study in 24 practices in Minnesota, which included a case manager function, showed improvements in both process and outcome 15 . Other interventions have resulted in improvement in process but not laboratory outcomes 8,10,16 . Systematic reviews suggest that quality improvement strategies in diabetes care produce modest results 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in 24 practices in Minnesota, which included a case manager function, showed improvements in both process and outcome 15 . Other interventions have resulted in improvement in process but not laboratory outcomes 8,10,16 . Systematic reviews suggest that quality improvement strategies in diabetes care produce modest results 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The Chronic Care Model highlights the importance of a population-based approach; involving community, patients and providers; and information technology [4][5][6] . Various combinations of population management, practice support, and patient outreach have been used for diabetes care in a variety of settings with mixed results [7][8][9][10][11][12][13][14][15][16] . Many practice interventions for diabetes have been carried out in academic and urban centers.…”
mentioning
confidence: 99%
“…13 The study from Phillips et al 14 and Ziemer et al 6 regarded the same study population, with different outcome measures. This also applies to the three studies of Cleveringa et al [15][16][17] and to the studies from Khan et al 18 and MacLean et al 19 Therefore eventually 20 RCTs were included. Ninety-five articles were excluded because of different reasons, for example, review article (n = 14), no RCT (n = 22), no CDSS used in the intervention (n = 26), glucose monitoring system (n = 10), or diabetes self-management program (n = 11) (Fig.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…I alle studiene hadde legene brukt diabetesskjema, i to av dem i samarbeid med sykepleier (16,17). Tid brukt pĂ„ opplaering lĂ„ pĂ„ rundt Ă©n time der dette ble rapportert.…”
Section: Resultaterunclassified
“…Mulighetene for bearbeiding av registrerte pasientdata varierte. Dette kunne vaere funksjoner som automatiske pĂ„minnelser til pasienten (18), pĂ„minnelser om innkalling til time (13,16,18), forslag om endringer i medisinering (14,18,20) og tilbakemelding om registrerte data for pasienten eller legepraksisen sammenliknet med andre (13,14,19). Inkluderte studier (n = 7)…”
Section: Resultaterunclassified